Upper limb prosthesis for patients with congenital or acquired deformity - Xavier, Ricardo Taoni [UNESP]; de Carvalho, Aparecido Augusto [UNESP]; Rohmer, Eric; Castro, Fabian [UNESP]; Boris, Fabio Agostinho [UNESP]; Codinhoto, José Paulo [UNESP]; Machado, Erica Regina Marani Daruichi [UNESP]; Sanches, Marcelo Augusto Assunção [UNESP] (Springer Nature, 2019)
A prototype of an upper limb prosthesis with a single control is presented in this paper. The prosthesis has 16 degrees of freedom, five fingers with independent joints and articulations in the hand’s palm, being able to reproduce movements of anthropomorphic and anthropometric joints and holds. A sensorized glove was used to generate a database for the bionic hand, with different types of movements. Tests were performed on volunteers with congenital and acquired deformities. The results showed that the upper limb prosthesis works adequately with both types of patients.
Keywords: Electromyography; Grasps; Social inclusion; Upper limb prosthesis